Unprotected left main intervention for surgery-ineligible patients with coronary artery disease—Usefulness of micro-CT images for stent. (15th October 2016) - Sueta, Daisuke; Arima, Yuichiro; Hokimoto, Seiji; Mukunoki, Toshifumi; Tabata, Noriaki; Akasaka, Tomonori; Sato, Takahiro; Otani, Jun; Ogawa, Hisao
Abstract: Background: Percutaneous coronary intervention (PCI) for unprotected left main truncus (LMT) lesions is controversial. Inoperable status with advanced age, renal dysfunction, frailty, or patient request may require an unprotected left main PCI. PCI for LMT is not recommended in the typical clinical situation; however, when it is the only feasible option, the performance is not bad. We demonstrated the result of a cobalt-chromium everolimus-eluting stent (CoCr-EES) in the LMT stenting and serial changes via micro-computed tomography (μCT). μCT is an established imaging technique used for high-resolution, non-destructive assessment of vascular samples. The technique has drawn increasing interest for investigations of atherosclerotic arteries in both humans and animal models. There are no reports regarding the linkage between clinical results and μCT images. Methods and results: Between January 2009 and December 2014, we recruited 118 consecutive, unprotected LMT stenting cases in our institution. We examined the clinical outcomes and angiographic results with a CoCr-EES compared with a first-generation drug-eluting stent. The primary endpoint of this registry was the rate of one-year major adverse cardiac events (MACE). The one-year MACE rate was 2.54%; this did not include the CoCr-EES. We established LMT bifurcation models (mini-crush and culotte) using a CoCr-EES and obtained μCT images of the CoCr-EES. The images showed no deformation or strut apposition. Conclusion: CoCr-EES performed well in LMT in our institution and according to μCT. μCT images may be useful for anatomical simulation in stent deployment.